Mental Emotional Disorders and Coping Strategies of University Student During COVID-19 Pandemic: A Mixed Methods Study - Ridwan Mochtar Thaha; Dicky Indirwan; Sudirman Nasir; Muhammad Rachmat (Jurnal Kesehatan Masyarakat, 2023)
At the beginning of 2020, the world was shocked by the COVID-19 outbreak which has hit almost all parts of the world. Student academic activities are faced with an online learning system and the adaptation of new habits. This caused a different response from each student. This study aims to analyze the coping strategy of the student-facing COVID-19 pandemic at the Public Health Faculty, Hasanuddin University. This research is a mix-method study conducted in September-October 2020, located at the Faculty of Public Health, Hasanuddin University. This study used a sequential explanatory strategy where quantitative data is collected and analyzed firs with 233 respondents by accidental sampling, followed by qualitative data with 12 respondents by purposive sampling. The results showed that the COVID-19 pandemic affects students psychologically. The results showed that as many as 121 people (51.9%) and there is two coping strategy. Problem-focused coping consists of seeking social support and planful problem solving and Emotional-focused coping that is distancing. The government and Public Health Faculty, Hasanuddin University can maximize the assistance provided in the form of psychological and financial assistance.